Sistem Pendukung Keputusan Pemberian Kartu Indonesia Pintar Berdasarkan Kriteria Kesejahtraan Keluarga dengan Menggunakan Metode Simple Additive Weighting - Maria Seran; Yohanis Malelak; Gregorius Rinduh Iriane (Universitas Kristen Immanuel, 2023)
This study discusses the Decision Support System for Giving KIP (Smart Indonesia Card), based on Family Welfare Criteria using the Simple Addtive Weighting (SAW) Method in Bakunase 2 Village, which does not yet exist and is applied using a computer so that it can simplify and speed up decision making. In making decisions, there are many problems that must be decided by looking at several criteria that must be possessed by students as a condition for obtaining KIP scholarships. The basic concept of the Simple Addtive Weighting method is to find the weighted sum of the performance branches on each alternative and all attributes. Simple Addtive Weighting was chosen because this method determines the weight value for each attribute, then proceeds with a ranking process that will select the best alternative from a number of alternatives, in this case the alternative in question is the feasibility of receiving KIP assistance in Bakunase 2. This study aims to build a system application Decision Support to help students get KIP scholarships. This application is expected to help and make it easier for students to get KIP scholarships.